Olives and olive oil in health and disease prevention - Preedy, Victor R.; Watson, Ronald Ross (London : Elsevier Publications, 2021)
'Long used in sacred ceremonies and associated with good health, the nutritional and health promoting benefits of olives and olive oils have been proven by an ever-increasing body of science. From cardiovascular benefits to anti-microbial, anti-cancer, antioxidant activity and effects on macrophages and aptoptosis to cellular and pathophysiollogical process, olives and olive oils are proving important in many healthful ways. For example, reactive components in olive oils or olive oil by-products have now been isolated and identified. These include tyrosol, hydroxytyrosol, 3,4-dihydroxyphenyl acetic acid elenolic acid and oleuropein. Oleic acid is the main monosaturated fatty acid of olive oil. These have putative protective effects and modulate the biochemistry of a variety of cell types including those of the vascular system. Some but not all components have been characterised by their putative pharmacological properties. It is possible that usage of these aforementioned products may have beneficial application in other disease. However, in order for this cross-fertilization to take place, a comprehensive understanding of olives and olive oils is required. Finding this knowledge in a single volume provides a key resource for scientists in a variety of food an nutritional roles'--
Includes bibliographical references and index.
Keywords: Plant Oils -- therapeutic use; Plant Oils -- chemistry; Dietary Fats, Unsaturated -- therapeutic use